Epistemologi Pembaharuan Usul Fikih Hasan Turabi: Epistemologi Pembaharuan Usul Fikih Hasan Turabi - Jamaluddin, Jamaluddin (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2017)
The article is the research result of the reform of Ushul Al Fiqh proposed by Hasan Turabi. The method applied is descriptive qualitative, exposing the entire ideas of Hasan Turbi pertaining to the reform of Ushul Fiqh and proceeded by the approach of content analysis. The next step is to make comparison with ideas of other Ushul Fiqh scholars. The reform of Ushul Fiqh according to Hasan Turbi is to implement qiyas al-wasi (wide qiyas) and istishab al-wasi (wide qiyas). The method applied by Hasan Turbi has already been used by former Ushul Fiqh scholars. Hasan Turbi only adds the words al-wasi. The essence of qiyas al-wasi and istishab al-wasi by Hasan Turabi is traditional issues already been done for a long time in a certain community or actual issues